School's out-- forever - Patterson, James, 1947- (New York : Warner Vision Books, 2007)
After a short stay with an FBI agent who gives them a chance to attend school and live a normal life, the six genetically-altered, winged youths head toward Florida and Max's ultimate destiny--to save the world, whether she wants to or not.
Young Adult
Young Adult
Keywords: Adventure and adventurers -- Juvenile fiction; Genetic engineering -- Juvenile fiction; Schools -- Juvenile fiction; Adventure and adventurers -- Fiction; Genetic engineering -- Fiction; Schools -- Fiction; Science fiction; Adventure fiction; Genetic engineering -- Fiction; School stories; Science fiction; Science fiction